2019
DOI: 10.1093/ofid/ofz479
|View full text |Cite
|
Sign up to set email alerts
|

The CHROME Study, a Real-world Experience of Single- and Multiple-Dose Oritavancin for Treatment of Gram-Positive Infections

Abstract: Background Oritavancin (ORI) is a long-acting lipoglycopeptide indicated for the treatment of adult patients with acute bacterial skin and skin structure infections (ABSSSIs) caused or suspected to be caused by susceptible Gram-positive (GP) pathogens. Methods Data collected from a retrospective observational program (2014–2017), Clinical and Historic Registry and Orbactiv Medical Evaluation (CHROME), describe the utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
2
35
0
5
Order By: Relevance
“…The reported results are encouraging, as success rates are comparable or exceed those observed with other commonly used agents 32–34 . A recent study reported oritavancin use in 440 patients for treatment of a variety of gram‐positive infections including bacteremia (n=7), OM (n=4), SA (n=3), and prosthetic joint infections (n=3) 35 . In many of these cases, oritavancin was used as salvage therapy after clinical failure with other agents.…”
Section: Long‐acting Lipoglycopeptidesmentioning
confidence: 79%
See 1 more Smart Citation
“…The reported results are encouraging, as success rates are comparable or exceed those observed with other commonly used agents 32–34 . A recent study reported oritavancin use in 440 patients for treatment of a variety of gram‐positive infections including bacteremia (n=7), OM (n=4), SA (n=3), and prosthetic joint infections (n=3) 35 . In many of these cases, oritavancin was used as salvage therapy after clinical failure with other agents.…”
Section: Long‐acting Lipoglycopeptidesmentioning
confidence: 79%
“…A phase II, randomized, controlled trial of 75 adult patients with catheter‐related BSIs showed higher success rates (combined clinical and microbiologic response) with two doses of dalbavancin than daily vancomycin (87.0% vs 50.0%) 28 . Similar success rates for bacteremia have been documented for oritavancin 61 Due to low cerebrospinal fluid penetration, central nervous system involvement in the infectious process should preclude the use of either laLGP agent (Daniel Read, PhD (Medical Science Liaison), written communication, Allergan [dalbavancin manufacturer], 3/29/2019) 62 …”
Section: Considerations For Selection Of Dalbavancin Versus Oritavancinmentioning
confidence: 94%
“…Oritavancin is a long-acting lipoglycopeptide antibiotic initially approved for the treatment of acute bacterial skin and skin structure infection (ABSSSI) and supported by the phase 3 SOLO program [ [8] , [9] , [10] , [11] ]. Its terminal half-life is 245 h. Dosage adjustments are unnecessary for patients with mild to severe renal or mild to moderate hepatic impairments [ [8] , [9] , [10] , [11] , [12] ]. Given its protein binding of 85 %, with a single dose of 1200 mg, the predicted free drug concentrations at seven days would exceed the breakpoints for labeled pathogens [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oritavancin exerts bactericidal activity against gram-positive bacteria, including E. faecalis and E. faecium , regardless of vancomycin susceptibility [ 14 ]. Phase 3 SOLO studies and real-world experience demonstrated the safety and tolerability of oritavancin [ [8] , [9] , [10] , [11] , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no randomized controlled trials have been conducted to assess oritavancin' s efficacy in off-label indications or continued dosing, but several case reports and retrospective cohort analyses show promising outcomes. [8][9][10][11][12][13][14][15][16] In an analysis of data from the Clinical and Historic Registry and Orbactiv Medical Evaluation (CHROME) patient registry, 32 patients received multiple doses of oritavancin for complicated Gram-positive infections with a 93.8% overall clinical success rate, including success rates of 90.9% (10/11) for general bone and joint infections and 87.5% (7/8) for patients diagnosed specifically with osteomyelitis. 8 Patients received between 2 and 10 doses of 1,200 mg IV given every 6 to 14 days.…”
Section: Efficacy Of Continued Dosingmentioning
confidence: 99%